The role of viral marketing in enhancing customer confidence: An analytical study of the opinions of a sample of managers of mobile phone companies in Iraq Zain, Asiacell, Korek, Our Contact - Alaa Farhan Talib; Abdel Fattah Jassim Zaalan; Faisal Alwan Al-Taie (Iraqi Journal for Administrative Sciences, 2024)
The study aimed to identify the role of each of the viral marketing strategy in promoting customer trust in the telecommunications sector in Iraq, through the use of modern and sophisticated techniques in contact with customers, launched the study of the problem has been expressed a number of intellectual and practical questions , been targeted answered clarify theoretical philosophy and connotations intellectual of the tow variables addressed by the study, namely, ( viral marketing and customer confidence), one of the modern general Arab environment especially the Iraqi and the environment spammers intellectual, and then diagnose the level of importance, impact and potential application in the telecommunications sector in Iraq, it was this study apply to mobile phone companies in Iraq (ether, Asia torrent, Cork, Itisaluna) through composed a sample of 100 member occupy managerial positions, questionnaire has been designed to collect the necessary data, and has emerged as the importance of the study of modern variables dealt with and that have not had sufficient attention to studying these variables and push them to try to study their impact on the various aspects of the work in service companies in Iraq, the independent variables on the dependent variable, the study reached a set of conclusions which my help companies to improve their performance and reach competitive centers, and on this basis The study came out a set of recommendations focused on the need for a whole benefit from the current study and reached in strengthening the competitive position of the sample companies through the optimal use and benefit from all of the social networking strategy and viral marketing and its role in enhancing the confidence of the customer netw.